Effect of structure parameters and composition of high-silica porous glasses on their thermal and radiation resistant properties - Antropova, Tatiana V.; Volkova, Anna V.; Petrov, Dmitry V.; Stolyar, Sergei V.; Ermakova, Ludmila E.; Sidorova, Marianna P.; Yakovlev, Evgeny B.; Drozdova, Irina A. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The influence of a composition of initial phase-separated alkali borosilicate glass and its thermal treatment as well leaching conditions on the parameters of the porous glass structure are discussed. The results obtained by adsorption and conductivity methods, transmission electron microscopy and dilatometer technique were used to analyse the effect of structure parameters and composition of high-silica porous glasses on their thermal and radiation resistant properties.
Optica Applicata, Vol. 35, 2005, nr 4, s. 717-723
Keywords: optyka; porous glass (structure, thermal and radiation resistant properties); electron microscopy; dilatometry